Prevalencia de lumbalgia mecánica en pacientes adultos con hiperlaxitud ligamentaria - Cabrera Pastor, Lourdes Helen (2019)
Objective: To determine the prevalence of mechanical low back pain in adult patients with ligament hypermobility. Material and Method: Descriptive, transversal study. A total of 217 medical records of patients aged between 18 and 40 years with diagnosis of ligament hypermobility attended at the Rheumatology Service of the Trujillo Regional 2 Teaching Hospital during the period January 2009 to December 2015. Results: Of the total sample, 173 were women (80%) and 44, men. The prevalence of mechanical lower back pain was 26%. Of the total of women, 27% developed mechanical lower back pain, while of men, only 23%. The age range was from 18 to 40 years, dividing it into three intervals (18-24, 25-30, 31-40 years); higher prevalence (29%) was found in the ages of 31-40 years. In addition, as the age increases, the prevalence is higher. Conclusions: The prevalence of mechanical lower back pain in adult patients with ligamentous hyperlaxity is 26% (56 patients), with predominance in the female population (27%) and in ages between 31-40 years (29%). In addition, other rheumatological pathologies were found in patients with ligamentous hyperlaxity, so it is recommended to perform other studies to check if there is an association between both diagnoses.